(untitled) (Journal Of Educational and Psychological Researches, 2022)
This study aims to identify the degree of students of Princess Rahma University College owning e-learning skills related to MOODLE as they perceived in the of light Corona crisis. The researchers’ questionnaire consisted of (37) items, distributed in three areas of e-learning skills related to the MOODLE on (147) students were chosen randomly. The results of the study showed that the degree of students ’possession of e-learning skills related to the MOODLE was significant. The results also revealed that there were statistically significant differences in the degree of students’ possession of electronic learning skills related to the MOODLE due to sex in favor of females. Finally, there were no statistically significant differences in the degree of students ’possession of e-learning skills related to the MOODLE due to the variable of specialization and academic level.